Numerical Investigation of Distribution Laws of Shear Force in Box Girder Webs - Xingwei Xue; Chao Zang; Junlong Zhou; Hai Zhang (Advances in Materials Science and Engineering)
To study the shear force distribution laws of a box girder with a single-box multichamber (SB-MC) configuration for different supporting conditions, numbers of webs, stiffness of end diaphragm, and web thickness values, a box girder with SB-MC was numerically simulated using three-dimensional finite element model. According to the comparison results of web shear force, the concept of η, a shear-increased coefficient for webs, was introduced. The results show that supporting conditions and chambers have a significant impact on the shear-increased coefficient η, and end diaphragm must be set up in the 3D finite element model when calculating η. Nonlinear analysis shows that in the elastic phase, the shear-increased coefficient η basically does not change, but in the cracking stage, the coefficient η of each web changes with the degree of web cracking, and side-webs (S-Webs) reach the ultimate load first. The variation of the web thickness hardly affects the distribution of the shear force, so the method to adjust the web thickness of S-Web was proposed according to the result of shear-increased coefficient η to improve the shear resistance of the box girder.